2015
DOI: 10.1097/md.0000000000001456
|View full text |Cite
|
Sign up to set email alerts
|

An Elevated Glycemic Gap is Associated With Adverse Outcomes in Diabetic Patients With Community-Acquired Pneumonia

Abstract: Several studies argue against the association between admission hyperglycemia and adverse outcomes in infected diabetic patients. When investigating the association, it is necessary to consider preexisting hyperglycemia. The objective of this study was to assess whether stress-induced hyperglycemia, determined by the glycemic gap between admission glucose levels and A1c-derived average glucose levels adversely affects outcomes in diabetic patients admitted to hospital with community-acquired pneumonia (CAP).We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
2
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 71 publications
5
34
2
3
Order By: Relevance
“…A history of DM but not hyperglycemia impacts the long-term mortality associated with AECOPD 26. Our previous work showed an association between elevated glycemic gaps and adverse outcomes in patients with DM presenting with liver abscesses, community- acquired pneumonia, and acute myocardial infarction, as well as the outcomes of critically ill patients who were admitted to intensive care units (ICUs) 1114. Consistent with these results, we again found that elevated glycemic gaps and modified stress hyperglycemia ratios were associated with the development of ARF in patients with DM during AECOPD.…”
Section: Discussionmentioning
confidence: 99%
“…A history of DM but not hyperglycemia impacts the long-term mortality associated with AECOPD 26. Our previous work showed an association between elevated glycemic gaps and adverse outcomes in patients with DM presenting with liver abscesses, community- acquired pneumonia, and acute myocardial infarction, as well as the outcomes of critically ill patients who were admitted to intensive care units (ICUs) 1114. Consistent with these results, we again found that elevated glycemic gaps and modified stress hyperglycemia ratios were associated with the development of ARF in patients with DM during AECOPD.…”
Section: Discussionmentioning
confidence: 99%
“…Thirteen studies reported data on inpatients [48][49][50][51][52][53][54][55][56]58,60,61,64], two on low-risk patients [44,57] and high-risk [57,63] patients and one on outpatients [54]. Pooled event rates were 4.5% (95% CI 2.9-6.5), 0.2 (95% CI 0-0.7), 1.6 (95% CI 0.1-4.9), and 0.9 (95% CI 0.5-1.8), respectively ( Figure 3).…”
Section: Acute Coronary Syndromesmentioning
confidence: 99%
“…This is in contrary to most previous results confirming the definitive negative prognostic role of glycemic gap and other SIH indices under varied disease setting like ICU, pyogenic liver abscess, community acquired pneumonia, trauma; such studies were lacking in diabetic hyperglycemic emergencies. [4][5][6][7] Nevertheless, the role of elevated glycemic gap and SIH in critically ill diabetics as well as hyperglycemic emergencies could not be entirely ruled out, as the current guidelines laid by the American College of Critical Care Medicine suggested intensive insulin therapy to maintain a tight glycemic control, thereby improving the clinical outcome of critically ill diabetics. 25…”
Section: Discussionmentioning
confidence: 99%
“…Glycemic gap has also been useful in predicting the unfavorable outcomes in diabetics with trauma and other diseases like pyogenic liver abscess, community acquired pneumonia. [5][6][7] The diagnosis and severity staging of diabetic hyperglycemic emergencies involve plasma glucose, serum osmolality, serum bicarbonate, arterial pH, anion gap, urine ketones, mental status. 2 The objective of this study is to determine the usefulness of glycemic gap as a prognostic indicator in acute hyperglycemic emergencies of T2DM.…”
Section: Introductionmentioning
confidence: 99%